KRITIK SASTRA MARXIS FREDRIC JAMESON: TEORI DAN APLIKASINYA - Ramayda Akmal (POETIKA, 2013)
AbstractThis paper is a review and preparation of concepts and ideas developed by Fredric Jameson in the realm ofliterature. From three main books, namely Marxism and Form, The Political Unconscious and Postmodern, or TheCultural Logic of Late Capitalism, Jameson this paper formulated the idea to produce a theoretical and methodologicalframework trace. With the same source as well, affecting the general idea and provide the basic foundation for thinkingJameson as Marxism, psychoanalysis and postmodernism will be presented.Keywords: Fredric Jameson, Marxism, Literary Works